Five‐Membered Ring Nitroxide Radical: A New Class of High‐Potential, Stable Catholytes for Neutral Aqueous Organic Redox Flow Batteries. (17th June 2021) - Hu, Bo; Fan, Hao; Li, Hongbin; Ravivarma, Mahalingam; Song, Jiangxuan
Abstract: The utilization of redox‐active and stable cyclic nitroxide radicals (CNRs) holds a great promise in neutral aqueous organic redox flow batteries (AORFBs) for large‐scale energy storage. Herein, a new class of CNRs with five‐membered ring pyrrolidine and pyrroline motifs for AORFBs is reported. By rational molecular engineering of introducing CC double bond into the pyrrolidine‐based molecule, 3‐carbamoyl‐2, 2, 5, 5‐tetramethylpyrroline‐1‐oxyl (CPL) with a high redox potential of 0.76 V (vs Ag/AgCl) is demonstrated, which is 160 mV higher than the common 2, 2, 6, 6‐tetramethylpiperidine 1‐oxyl derivatives with a six‐membered ring as the core structure. Density functional theory calculations reveal that the much enhanced redox potential for CPL is largely contributed by lowered standard free energy in reduction reaction and charge population sum of NO radical head. When paired with the BTMAP‐viologen anolyte, the CPL‐based AORFB delivers constant capacity retention of up to 99.96%/cycle over 500 cycles. Abstract : A new class of nitroxide radicals with a five‐membered ring structure is first reported as novel catholyte alternatives for aqueous redox flow batteries. The five‐membered pyrroline nitroxide radical exhibits a redox potential up to 0.76 V, 160 mV higher than that of the six‐membered 2, 2, 6, 6‐tetramethylpiperidine 1‐oxyl derivative with the same carbamoyl substituent.